Thermal Digital Twin of LH2 Aircraft Storage Tank - Carles Oliet; Marcial Mosqueda-Otero; Eugenio Schillaci; Ahmad Amani; Joaquim Rigola; Jesús Castro (Engineering Proceedings)
The decarbonization of the economy is impacting all activities and sectors worldwide. Transport, particularly aircraft transport, is involved in this endeavor; shifting to H2-powered aircraft is one of the identified options for decarbonization, which implies the need for the effective implementation of complex cryogenic LH2 storage. Modeling tank storage via a Digital Twin (DTwin) is of paramount relevance to facilitate the design process (gains, operating scenarios) and for the extrapolation of experimental measurements on a particular set-up to future tanks with other materials or dimensions. The present paper contributes to this issue, presenting the model under development as part of the H2ELIOS project and the preliminary model results.